2014
DOI: 10.1073/pnas.1322671111
|View full text |Cite
|
Sign up to set email alerts
|

Effector MiSSP7 of the mutualistic fungus Laccaria bicolor stabilizes the Populus JAZ6 protein and represses jasmonic acid (JA) responsive genes

Abstract: Ectomycorrhizal fungi, such as Laccaria bicolor, support forest growth and sustainability by providing growth-limiting nutrients to their plant host through a mutualistic symbiotic relationship with host roots. We have previously shown that the effector protein MiSSP7 (Mycorrhiza-induced Small Secreted Protein 7) encoded by L. bicolor is necessary for the establishment of symbiosis with host trees, although the mechanistic reasoning behind this role was unknown. We demonstrate here that MiSSP7 interacts with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
285
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(294 citation statements)
references
References 36 publications
3
285
0
Order By: Relevance
“…This finding suggests a lessor control by the plant over R. irregularis colonization that may be related to the fungal ability to suppress or evade the plant defense response, thus achieving a higher root invasion (Campos-Soriano et al 2010). Indeed, it has been reported that R. irregularis can deliver the effector protein SP7, which attenuates the plant immune response that enables the accommodation of the fungus within plant roots (Kloppholz et al 2011), as it occurs in ectomycorrhizas (Plett et al 2014b). How conserved and efficient this mechanism is in other AMF remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests a lessor control by the plant over R. irregularis colonization that may be related to the fungal ability to suppress or evade the plant defense response, thus achieving a higher root invasion (Campos-Soriano et al 2010). Indeed, it has been reported that R. irregularis can deliver the effector protein SP7, which attenuates the plant immune response that enables the accommodation of the fungus within plant roots (Kloppholz et al 2011), as it occurs in ectomycorrhizas (Plett et al 2014b). How conserved and efficient this mechanism is in other AMF remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An improved understanding of the ability of ECM fungi to decompose lignocellulose is needed to resolve mechanisms of nutrient cycling in forests. The ECM lifestyle in Laccaria bicolor is associated with the expression of new mycorrhizainduced small secreted proteins (MiSSPs) that are required for establishment of symbiosis 11,12 . Mycorrhizal symbioses have arisen repeatedly during fungal evolution and include not only ECM associations but also those with ERM and ORM mycorrhizae 13 .…”
mentioning
confidence: 99%
“…In L. bicolor, symbiosis requires lineage-specific genes encoding small secreted effector proteins that control host-plant development and immunity 4,11,12 . By sequencing RNA from free-living mycelia and mycorrhizal roots, we identified genes regulated by symbiosis development in the ECM A. muscaria, H. cylindrosporum, P. involutus, Piloderma croceum and Suillus luteus, the ERM O. maius and the ORM S. vermifera and T. calospora.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some strains of the hemibiotrophic bacterial pathogen Pseudomonas syringae have evolved an ability to produce a potent JA-mimicking phytotoxin, coronatine (COR), to activate JA signaling as an effective means of inhibiting SA defense and promote plant susceptibility (4,26,28,29). Furthermore, CORlike compounds are produced by pathogens of other taxa (30,31) and proteinaceous effectors from both bacterial and fungal pathogens have been shown to target the COI1-JAZ coreceptor (32)(33)(34). These recent findings suggest that the COI1-JAZ coreceptor is a common target of manipulation by diverse plant pathogens and represents a prominent vulnerable point of the plant immune network.…”
mentioning
confidence: 99%